The impact of adult children’s support on the psychological health of rural older adult people in China - Luo, Juan; Ji, Minglu; Li, Mengyuan; Wang, Anning (Frontiers in Public Health, 2023)
Background Family old-age care is dominant in Chinese rural society, and children’s support is an important force in family old-age care. However, the migration of a large number of young and middle-aged rural laborers has undermined the traditional arrangements for old-age care in rural areas and affected the psychological health of the older adult. Methods 2014 China Longitudinal Aging Social Survey targets Chinese citizens aged 60 or older and covers 28 provinces in mainland China. In this paper, the database of the CLASS was selected for empirical analysis to explore the impact of children’s support on the depression level and loneliness of rural older adults through multiple linear regression, and was divided into two groups according to children’s migration to analyze heterogeneity. Results Children’s financial support facilitates the maintenance of mental health among rural older adults. Children’s support promotes mental health among rural older adults, but this association does not exist among older adults without children’s migration. Individual characteristics of older people have a greater impact on mental health. Discussion Our study firstly compares the differences of children’s migration status between children’s support and mental health among the older adult in rural China. In order to improve the mental health of the older adult, it is necessary to create a favorable atmosphere of love and respect for the older adult, improve the social security system in rural areas, and give full play to the strengths of the social forces, so as to ensure that the older adult have a sense of worthiness and enjoyment in their old age.